Development and Evaluation of a Virtual Reality Puzzle Game to Decrease Food Intake: Randomized Controlled Trial - Yunxin Liu; Angelos Stamos; Siegfried Dewitte; Zeph M C van Berlo; Laura N van der Laan (JMIR Publications, 2022)
BackgroundVirtual reality (VR) has gained popularity in daily life, and VR food cues seem to elicit food cravings, similar to real food cues. However, little is known about the impact of VR food cues on actual food intake. ObjectiveIn real life (RL), exposure to food cues in a situation in which the desire to eat food interferes with the completion of a food-related task reduces the subsequent food intake (ie, the pre-exposure effect). In this study, we examine, on the one hand, whether the pre-exposure effect could be replicated in RL and, on the other hand, whether this effect could be extended to VR contexts. MethodsThe study used a 2 (stimulus type: food vs nonfood) × 2 (mode: VR vs RL) between-subject design (n=175). Participants were randomly assigned to 1 of the 4 conditions. ResultsWe found the main effect of mode on food intake, with a higher food intake after both VR conditions than after RL conditions (P=.02). In addition, among female participants, we found that exposure to both food cues (ie, VR and RL) resulted in lower food intake than exposure to both nonfood cues (P=.05). In contrast, this effect was not observed among male participants (P=.34). Additionally, VR and RL cues generated similar emotional and behavioral responses (eg, arousal and game difficulty). ConclusionsWe were unable to replicate the exposure effect in our complete sample. Subgroup analyses, however, showed that for women, exposure to food cues (either in VR or in RL) reduces food intake, indicating that a VR pre-exposure procedure may effectively be applied exclusively for women. Trial RegistrationClinicalTrials.gov NCT05169996; https://clinicaltrials.gov/ct2/show/NCT05169996